A prospective study of nonmedical use of prescription opioids during adolescence and subsequent substance use disorder symptoms in early midlife. (1st January 2019) - McCabe, Sean Esteban; Veliz, Philip T.; Boyd, Carol J.; Schepis, Ty S.; McCabe, Vita V.; Schulenberg, John E.
Highlights: Adolescents' proper medical prescription opioid use was not related to later SUD. Adolescents' nonmedical use of prescription opioids (NMUPO) is heterogeneous. Medical prescription opioid use after NMUPO places youth at high-risk for later SUD. NMUPO motivated by pain relief during adolescence predicted later SUD at age 35. NMUPO characteristics can be used to screen high-risk adolescents for interventions. Abstract: Background: This longitudinal study assesses characteristics associated with adolescents' nonmedical use of prescription opioids (NMUPO) including: frequency, co-ingestion, motives, specific opioid type; sequence of initiation of medical use of prescription opioids and NMUPO in relationship to subsequent substance use disorder (SUD) symptoms. Methods: Twenty-one independent national cohorts of U.S. high school seniors (n = 8, 373) were surveyed and followed 17 years from adolescence to age 35. Results: The majority of adolescents who engaged in NMUPO reported occasional/frequent NMUPO, non-pain relief motives for NMUPO, simultaneous co-ingestion involving NMUPO and other drugs, opioid analgesics with high misuse potential, and multiple types of opioid analgesics. Adolescents who reported NMUPO for pain relief, NMUPO involving opioid analgesics with high misuse potential, or multiple prescription opioids had significantly greater odds of SUD symptoms at age 35, relative to those who had no history of NMUPO during adolescence. In addition, medical use of prescription opioids after initiating NMUPO (or NMUPO only) during adolescence was associated with significantly greater odds of subsequent SUD symptoms at age 35 relative to those who reported the medical use of prescription opioids only or had no medical use or NMUPO during adolescence. Conclusions: This is the first U.S. national prospective study to examine the relationships between adolescents' NMUPO characteristics and later SUD symptoms in early midlife. Several characteristics (frequency, co-ingestion, motives, opioid type, and medical/NMUPO initiation history) were identified that could be used to screen and detect high-risk youth for indicated interventions to reduce prescription opioid misuse and SUDs.